Health Literacy in Turkish Pregnant Women in the Framework of Prenatal Attachment and Coping Styles With Stress - Arzu Kul Uçtu; Veysel Kaplan (Gonabad University of Medical Sciences, 2023)
Background: Prenatal attachment affects maternal and infant health throughout life. Therefore, it is necessary to investigate the variables that may affect prenatal attachment. This study was carried out to investigate prenatal attachment, health literacy, and coping styles with stress among Turkish pregnant women by structural equation modeling. Methods:This is a descriptive, analytical, and cross-sectional study. It was conducted via a face-to-face interview with 420 pregnant women in a university hospital in Southeastern Turkey between May 15 and July 2022. The research analysis used a structural equation modeling using SPSS software, version 22 and AMOS software, version 23. Results: We found that the prenatal attachment levels of the pregnant women had a weak positive relationship with seeking social support and submissive approach styles, a moderate positive relationship with the optimistic approach styles, and a strong positive relationship with the self-confident approach styles (P<0.001). Also, there was a weak positive correlation between the prenatal attachment levels of the pregnant women and the subscales of understanding the information and appraisal/evaluation of the health literacy scale (P<0.001). Conclusion: There is a strong relationship between prenatal attachment, coping styles with stress, and the number of births. Also, health literacy and stress coping styles were effective variables in prenatal attachment. Therefore, it is very important to enrich the knowledge of women about their health during pregnancy.